Urbanised society in the age of cities: Spatial governance for transforming the urban space - Olcar, Cumhur (New York Routledge, 2025)
This book details the transformation processes that impinge on constitutionally ordained governance by drawing on the new theoretical approaches in the urban sciences. It is unique in terms of its focused content, which thoroughly analyses the transformation of space and governance in Turkey and beyond and how urban institutions have emerged and changed since their inception.
Keywords: Urban Society; Social Science; Transforming India